The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1039/c7cp07770j
|View full text |Cite
|
Sign up to set email alerts
|

Gas phase 1H NMR studies and kinetic modeling of dihydrogen isotope equilibration catalyzed by Ru-nanoparticles under normal conditions: dissociative vs. associative exchange

Abstract: The equilibration of H2, HD and D2 between the gas phase and surface hydrides of solid organic-ligand-stabilized Ru metal nanoparticles has been studied by gas phase 1H NMR spectroscopy using closed NMR tubes as batch reactors at room temperature and 800 mbar. When two different nanoparticle systems, Ru/PVP (PVP ≡ polyvinylpyrrolidone) and Ru/HDA (HDA ≡ hexadecylamine) were exposed to D2 gas, only the release of HD from the hydride containing surface could be detected in the initial stages of the reaction, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 64 publications
(47 reference statements)
3
20
0
Order By: Relevance
“…Ligand separated nanoparticles catalyze a number of chemical reactions, e. g. hydrogenation of olefins and C−C activation . In combined 1 H gas phase and solid state 2 H NMR studies, some of us have shown that these particles contain surface hydrogens, which can be replaced by deuterons by exposure to D 2 gas, resulting in the release of HD. However, it was also observed that CH 2 groups of organic ligands such as hexadecylamine (HDA) were partially deuterated, a process which could only take place via C−H activation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ligand separated nanoparticles catalyze a number of chemical reactions, e. g. hydrogenation of olefins and C−C activation . In combined 1 H gas phase and solid state 2 H NMR studies, some of us have shown that these particles contain surface hydrogens, which can be replaced by deuterons by exposure to D 2 gas, resulting in the release of HD. However, it was also observed that CH 2 groups of organic ligands such as hexadecylamine (HDA) were partially deuterated, a process which could only take place via C−H activation.…”
Section: Methodsmentioning
confidence: 99%
“…In the first step (see Scheme S1a), surface hydride of the latter – which contain a large number of defects such as edges, apexes and steps that offer coordinatively unsaturated metal atoms – are deuterated releasing HD when they are exposed to D 2 gas . In the second step, the alkane substrate forms a σ‐complex with surface Ru atoms and transfers an H from C to Ru (Scheme S1b) corresponding to an oxidative cleavage of a surface alkyl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks are broader as compared to the liquid state because of efficient longitudinal and transverse spin‐rotation and dipolar relaxation mechanisms arising from the coherent and incoherent molecular rotation in the gas phase. This effect is stronger for small molecules such as HD, and even more pronounced for H 2 ,. In contrast to the Pt‐containing NPs, the spectra of the Ru‐containing NPs present an additional signal around 0.1 ppm.…”
Section: Resultsmentioning
confidence: 92%
“…For MNPs formed by hydrogenation of organometallic precursors it has been shown by a combination of 1 H gas phase and solid state 2 H NMR that hydrides are present on the surface of the particles and that they are mobile and exchangeable by deuterium . Recently, some of us have explored the kinetics of gas‐solid hydrogen isotope exchange of ruthenium metal nanoparticles (RuMNPs) in more detail . It was found that when D 2 is applied to RuMNPs, a direct reaction with surface hydrides occurs without D 2 dissociation leading to the formation of HD in the initial reaction stages.…”
Section: Introductionmentioning
confidence: 99%